2023
DOI: 10.3389/fcimb.2023.1179958
|View full text |Cite
|
Sign up to set email alerts
|

A novel risk classifier to predict the in-hospital death risk of nosocomial infections in elderly cancer patients

Abstract: BackgroundElderly cancer patients are more predisposed to developing nosocomial infections during anti-neoplastic treatment, and are associated with a bleaker prognosis. This study aimed to develop a novel risk classifier to predict the in-hospital death risk of nosocomial infections in this population.MethodsRetrospective clinical data were collected from a National Cancer Regional Center in Northwest China. The Least Absolute Shrinkage and Selection Operator (LASSO) algorithm was utilized to filter the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…We identified several predictors that were associated with the risk of arthritis in community-dwelling middle-aged and older adults. We found that the combination index outperformed a single marker in terms of predictive ability [ 51 ]. Therefore, we developed a nomogram based on these variables to predict the risk of arthritis in community-dwelling middle-aged and older adults.…”
Section: Discussionmentioning
confidence: 99%
“…We identified several predictors that were associated with the risk of arthritis in community-dwelling middle-aged and older adults. We found that the combination index outperformed a single marker in terms of predictive ability [ 51 ]. Therefore, we developed a nomogram based on these variables to predict the risk of arthritis in community-dwelling middle-aged and older adults.…”
Section: Discussionmentioning
confidence: 99%